F-Exponential - Conceição, Ana C. (2013)
The article (see http://hdl.handle.net/10400.1/1105) was first presented in the 1st National Conference on Symbolic Computation in Education and Research, IST Portugal 2012, where distinguished with the Timberlake Award for Best Article by a Young Researcher. On how to work with the CDF format please see http://www.wolfram.com/cdf-player/.